2017
DOI: 10.1038/srep39912
|View full text |Cite
|
Sign up to set email alerts
|

Increased Uterine NK cell numbers and perforin expression during the implantation phase in IVF Cycles with GnRH Antagonist Protocol

Abstract: GnRH antagonist negatively affects endometrial receptivity in in vitro fertilization (IVF) cycles, however, its underlying mechanism remains unclear. To explore its target molecules, we studied endometria in the window phase of fixed GnRH antagonist, low-dose flexible GnRH antagonist, GnRH agonist long protocol, and untreated control groups. There were 384 differentially expressed genes (DEGs) in the fixed antagonist group with greater than twofold expression change compared with the control group and 197 DEGs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 43 publications
1
22
1
Order By: Relevance
“…Some studies have suggested that there are lower implantation rates for the GnRH-ant protocol than for the GnRH-a protocol due to differences in endometrial receptivity [23,32]. However, in our study, the implantation rates did not differ among the three ovarian hyperstimulation protocols, regardless of the POSEIDON group.…”
Section: Agingcontrasting
confidence: 83%
See 1 more Smart Citation
“…Some studies have suggested that there are lower implantation rates for the GnRH-ant protocol than for the GnRH-a protocol due to differences in endometrial receptivity [23,32]. However, in our study, the implantation rates did not differ among the three ovarian hyperstimulation protocols, regardless of the POSEIDON group.…”
Section: Agingcontrasting
confidence: 83%
“…However, the effectiveness and reliability of the GnRHant protocol are still debated [20,21]. In several recent trials and meta-analyses, lower pregnancy rates and higher cancelation rates were observed with the GnRHant protocol than with the GnRH-a long protocol [22] or the GnRH-a short protocol, especially in patients with < 4 oocytes retrieved in previous controlled ovarian stimulation cycles or in those with expected POR, raising concerns about the effectiveness of the GnRHant protocol in poor ovarian responders [4,23]. A series of studies suggested that the adverse effect of the GnRH-ant on endometrial receptivity is the main reason for the lower pregnancy and clinical pregnancy rates with this protocol [24,25], and this proposal warrants further investigation.…”
Section: Agingmentioning
confidence: 99%
“…A series of recent studies has confirmed that the adverse effects of GnRH-ant on endometrial receptivity were the main reason for this difference in pregnancy rate (4). Furthermore, in our previous studies we demonstrated the dose-related harmful effects of GnRH-ant on endometrial receptivity (6, 7).…”
Section: Introductionmentioning
confidence: 73%
“…Furthermore, Group 1 had a notable reduction in GnRH-ant consumption and reduced duration of stimulation compared with Group 2; this might result in improved pregnancy outcomes in Group 1. Many studies have reported that GnRH-ant is unfavorable for endometrial receptivity (4, 22), and our previous studies also found that antagonists caused uterine natural killer (uNK) cells and inflammatory factors such as perforin and tumor necrosis factor α (TNFα) to increase in a dose-dependent manner (6, 7). Furthermore, prolonged ovarian stimulation was associated with a decreased rate of superior-quality embryos and lower implantation, and live birth rates (2325).…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been also associated with less successful embryo implantation and live birth rates, mainly caused by lower endometrial receptivity (Kdous, Chaker, Bouyahia, Zhioua, & Zhioua, ). A possible cause for this failure could be the fact that CD95L protein expression is increased in the endometrium of patients treated with GnRH antagonists, concomitant with higher levels of 17β‐estradiol, responsible for up‐regulation of CD95L mRNA and cytotoxicity of NK cells (Hao et al, ; Xu et al, ). Melatonin has also been used to improve the ratio of successful implantations in IVF procedures.…”
Section: Introductionmentioning
confidence: 99%